Case 3852: Syntormon Loew, 1857 (Diptera, Dolichopodidae): proposed determination of neuter gender - Drake, C Martin; Welter-Schultes, Francisco (Bulletin of Zoological Nomenclature)
Noticed in BZN 78 (30 Apr 2021): 3.